Strategi Kodim 1703/Manokwari Dalam Penanganan Konflik Sosial di Provinsi Papua Barat - Uchaimid Biridlo'i Robby; Dedi Akhiruddin (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2021)
The level of pluralism of the Indonesian nation, which has a variety of religions, cultures, languages ​​and ethnicities, makes the Unitary State of the Republic of Indonesia a heterogeneous country, so it is common for friction to occur and cause social conflict by directing the masses to act irrationally. Conflict situations tend to be easily exploited by those who try to take advantage of them. Conflict parties have different understandings about the problems at hand. From this explanation explicitly, the importance of the involvement of Kodim 1703 / Manokwari of West Papua Province in dealing with social conflicts cannot only be borne by the handling of conflicts that have occurred but is an initial form of a persuasive approach to all elements of society. needed. This study aims to identify and analyze the strategy of Kodim 1703 / Manokwari of West Papua Province in handling social conflicts based on Law of the Republic of Indonesia Number 7 of 2012 in handling social conflicts in Indonesia, especially West Papua Province. The method used by the writer is descriptive qualitative method. The data obtained came from interviews with informants who were directly involved in the field during the handling of social conflicts in Manokwari. Based on the research results, it can be concluded as follows: (1) The role of Kodim 1703 / Manokwari in handling social conflicts in Manokwari City is limited by Law Number 7 of 2012 concerning Social Conflict Handling so that it is not optimal by involving all levels of society so that no one feels left out or ignored. Keywords: Management Strategic and Social Conflict